Street Lighting and Crime in Madison, WI - Elifritz, Trevor; Crump, Naomi; Knuth, Dan (My University, 2014)
Much academic literature exists which suggests street lighting acts to deter crime. This analysis offers a GIS approach to the spatial relationships between person-on-person and person-on-property crime with street lighting in downtown Madison, Wisconsin. In this report, it is hypothesized that streets with higher densities of street lighting will correspond with lower crime density. By combining calls for service to the Madison Police Department with city maintained street light shapefiles, the densities of crime and lighting per 200 feet along streets were calculated, and their relationships examined. In doing, a moderate correlation between high lighting density and high crime density is observed. We believe that because of data limitations, our site setting of the most heavily trafficked areas in Madison led to such a counterintuitive result.
Includes Maps, Figures, Illustrations and Bibliography.
Keywords: Crime; Madison; Street lighting